Letters to the Editor from O. W. Samson, Ernst Emsheimer, Bertil Soderberg, Paul Collaer, Michael G. M. Lane, Douglas Cleverdon, H. Hickmann, H. Pepper, J. K. Louw, Philip Gbeho, John T. Carrington, A. P. Atkins and H. H. Bloomfield - Tracey, Hugh (International Library of African Music, 1954)
pages: 80-83
Keywords: African Music